Effect of Mold Coating on Shell Morphology in Solidification - Turgut, M. Nurullah; Demir, M. Hakan; Yigit, Faruk (TRANS TECH PUBLICATIONS LTD, 2012)
The mold-shell interface plays a very important role during the earliest stages of metal casting processes. Heat is extracted from the molten metal through this interface resulting in the growth of the shell. Small spatial variations in heat extraction can lead to shell morphological instability where certain regions of the solidification front grow preferentially over others. This may cause cracks in the shell which can greatly reduce the integrity of the final cast product. Mold coating at the mold-shell interface is one of the most important factors controlling the heat transfer and, hence, it has very important role on the solidification rate and development of microstructure. In this paper, a linear perturbation method is used to solve a two-dimensional heat conduction problem in which a liquid, becomes solidified by heat transfer to a planar mold of finite thickness. The influence of physical parameters such as the coating material thickness, conductivity and thermal contact resistance on the growth of solidified shell thickness is investigated. The present work can form the thermal part of a subsequent investigation of related thermo elastic stress problems.
Keywords: Solidification; Growth; Instability; Phase-change; Perturbation; Engineering; Materials Science